The american solidarity in times of Covid-19: the blockade of Cuba - Antialón Conde, Alexander (2020)
Recently, there was an embargo on the necessary health materials to face the Covid-19 pandemic, to the detriment of Cuba, a country that faces 58 years of blockade by the United States, which revealed regionalindifference as well as serious deficiencies in the way the inter-American system has been conducted.